Botswana : Technical Assistance Report-National Accounts Mission. (IMF Staff Country Reports; Country Report, 2021)
A remote technical assistance (TA) mission was conducted by IMF's Regional Technical Assistance Center for Southern Africa (AFS)1 during April 12-16, 2021 to assist Statistics Botswana (SB) in improving the quality of the national accounts statistics. Reliable national accounts are essential for informed economic policymaking by the authorities. It also provides the private sector, foreign investors, rating agencies, donors and the public in general with important inputs in their decision-making, while informing economic analysis and IMF surveillance. The System of National Accounts, 2008 (2008 SNA) recommends that the national accounts be rebased every five years. Rebasing requires comprehensive surveys and ideally, supply and use tables (SUTs) to support coherent checking of data.